Collected poems and songs of George Campbell Hay (Deòrsa Mac Iain Dheòrsa). - Hay, George Campbell (Published for the Lorimer Trust by Edinburgh University Press, 2000)
The work of a highly significant figure in the renaissance of Gaelic poetry in the twentieth century is gathered together for the first time in one authoritative volume. George Campbell Hay's complete original poems, in Gaelic, Scots, English, French, Italian and Norwegian, are presented chronologically with accompanying English translations and annotations to each poem.This edition also includes a detailed biography, drawing on Hay's own correspondence, which sheds new light on the social, political and literary context of his work; an outline of Hay's main poetic concerns in theme and in form; and some of Hay's own musical settings.Hardback still available in deluxe 2-volume set.